Associations Among Physical Education, Activity-Related Healthy Lifestyle Practices, and Cardiorespiratory Fitness of Chinese Youth. Issue 2 (3rd April 2019) - Li, Youfa; Wang, Sijia; Yu, Yong; Wu, Lili; Shi, Yutong; Zhang, Michelle; Wu, Xinwei; Ma, Xiao
ABSTRACT: Purpose : Physical education (PE) in school provides opportunities for physical activity (PA) engagement and reportedly results in improved health-related fitness. This study explored the underlying correlations between PE and activity-related healthy lifestyle practices with current level of cardiorespiratory fitness.Methods : A total of 13, 138 students age 14 (boys = 7, 094, 54.0%) in Grade 8 from the China National Assessment of Educational Quality - Physical Education & Health 2015 were included in this study. Two independent structural equation modeling (SEM) analyses were conducted to obtained sex-specific results. Data included the results of the 15-m progressive aerobic cardiovascular endurance run (PACER) and questionnaire data regarding PE curriculum implementation, learning and practice, perceived support from PE teachers, PE facilities, PE equipment, activity-related healthy lifestyle practices, habitual physical fitness, appropriate method of physical fitness, and breakfast eating habits. Structural equation modeling was applied to examine the associations between variables, controlling for socioeconomic status, the location of schools, and Body Mass Index.Results : There was a statistically significant relationship between cardiorespiratory fitness and activity-related healthy lifestyle practices, which was somewhat positively impacted by skill learning and practice and perceived support from PE teachers. Together, the boy's model explained 21.8% of the variance in cardiorespiratory fitness, whereas the girl's model explained 15.9%.Conclusions : A well-organized PE program is related to students' activity-related healthy lifestyle practices, and consequently provides an improvement to cardiorespiratory fitness.